2018
DOI: 10.1103/physrevd.98.035040
|View full text |Cite
|
Sign up to set email alerts
|

Chromomagnetic and chromoelectric dipole moments of the top quark in the fourth-generation THDM

Abstract: The chromomagnetic dipole moment (CMDM) and chromoelectric dipole moment (CEDM) of the top quark are calculated at the one-loop level in the framework of the two-Higgs doublet model with four fermion generations (4GTHDM), which is still consistent with experimental data and apart from new scalar bosons (H 0 , A 0 , and H ± ) and quarks (b and t ) predicts new sources of CP violation via the extended 4 × 4 CKM matrix. Analytical expressions for the CMDM and CEDM of a quark are presented both in terms of Feynman… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 123 publications
0
16
0
Order By: Relevance
“…In addition, appreciable new physics effects on the top CEDM are of great importance as they would directly impact the CP-violation phenomenon, which would be indicative of new sources of CP violation and, in our case, of FV. Currently, the spin correlations of top-antitop pairs and the polarization of the top quark have been measured in pp collisions at ffiffi ffi s p ¼ [31] as well as in other extensions such as the two-Higgs doublet model [32], the minimal supersymmetric Standard Model [33,34], 3-3-1 models [35], technicolor models [36], models with vectorlike multiplets [37], effective operators [38], and the two-Higgs doublet model with four fermion generations [39]. However, the SM CMDM contribution of the top quark coming from the three-gluon vertex is in fact divergent when the gluon is on shell, but in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, appreciable new physics effects on the top CEDM are of great importance as they would directly impact the CP-violation phenomenon, which would be indicative of new sources of CP violation and, in our case, of FV. Currently, the spin correlations of top-antitop pairs and the polarization of the top quark have been measured in pp collisions at ffiffi ffi s p ¼ [31] as well as in other extensions such as the two-Higgs doublet model [32], the minimal supersymmetric Standard Model [33,34], 3-3-1 models [35], technicolor models [36], models with vectorlike multiplets [37], effective operators [38], and the two-Higgs doublet model with four fermion generations [39]. However, the SM CMDM contribution of the top quark coming from the three-gluon vertex is in fact divergent when the gluon is on shell, but in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…See for instance Ref. [12], where we performed the calculation of the electroweak contribution to the CMDM of quarks in the conventional linear R ξ gauge and verified that the gauge parameter ξ drops out from the result. Furthermore, the dipole form factors cannot receive contributions from self-energy diagrams, which are required to cancel gauge dependent terms appearing in the monopolar terms via the PT approach.…”
Section: Cmdm and Cedm Of The Top Quark In The Rm331mentioning
confidence: 68%
“…In summary, the real part of the new contribution of the RM331 can be of the same order of magnitude than the real part of the pure electroweak contribution of the SM [12]. Therefore the RM331 could give a contribution larger than the ones arising in other extension models (see for instance Ref.…”
Section: Figmentioning
confidence: 95%
See 1 more Smart Citation
“…Reference [6] showed that the type-II 2HDM with a sequential fourth generation satisfies not only the Higgs signal strength measurements but also the oblique parameters ΔS and ΔT. Follow-up studies focused on top-quark dipole moments [13], dark matter [14], and lepton flavor changing in the Higgs boson decays [15].…”
Section: Introductionmentioning
confidence: 99%